High-elasticity RAG: W elastic ceramic, preparation method and application

Through the preparation method of RAG:W elastic ceramics, combined with the AM gel injection molding process and the combination of inorganic calcium carbonate oligomers and organic covalent lipoic acid, the brittleness and low transmittance of traditional ceramic materials in the field of optical sensors is solved, and the combination of high transmittance and good elastic properties is achieved. It is suitable for applications in complex shapes and high mechanical stresses.

CN119899033APending Publication Date: 2025-04-29HENAN UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510124808.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The application of traditional ceramic materials in the field of optical sensors is limited by their brittleness and low transmittance, and it is difficult to meet the comprehensive requirements of high transmittance and elastic properties.

Method used

Using the preparation method of RAG:W elastic ceramics, RAG:W elastic ceramics with high elastic modulus were prepared by AM gel injection molding process and the combination of inorganic calcium carbonate oligomer (CCO) and organic covalent lipoic acid (TA).

Benefits of technology

The combination of high transmittance and good elastic properties of ceramic materials in the field of optical sensors is achieved, and the material's resistance to deformation and reliability is improved. It is suitable for applications in complex shapes and high mechanical stresses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899033A_ABST
    Figure CN119899033A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of high-elasticity RAG: W elastic ceramic. A method of combining AM gel casting with inorganic calcium carbonate oligomer (CCO) and organic covalent lipoic acid (TA) is utilized to solve the problem of poor elasticity of conventional ceramics. The method comprises the following steps: adding W oxide into mixed powder containing RAG, adding an inorganic calcium carbonate oligomer and organic covalent lipoic acid into an ethanol solution, adding the solution into the mixed powder, and carrying out AM gel injection molding to prepare RAG: W ceramics with different elasticity. Adding an AM monomer, a dispersing agent and a PH regulator into the ceramic powder, and carrying out ball milling to prepare slurry; injecting the slurry into a mold for solidification molding, demolding and drying to obtain a ceramic biscuit; and sintering, annealing and polishing the ceramic biscuit to obtain the RAG: W elastic ceramic. The RAG: W elastic ceramic has good elastic performance and can be applied to the field of optical sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optical functional elastic ceramics, and in particular relates to a high-elasticity RAG:W elastic ceramic, a preparation method and an application thereof. Background Art

[0002] Traditional transparent materials such as glass, although they have good optical transparency, are brittle and have poor impact resistance. They are easily broken when subjected to external forces, which limits their application in some special fields. Ceramics usually have high hardness and strength, but ordinary ceramics have poor transmittance and lack elasticity, which makes it difficult to meet the scenes with high requirements for the combination of optical and mechanical properties, limiting their development in some special fields.

[0003] With the development of science and technology, the demand for materials with both high transmittance and elasticity is growing in the field of optical sensors. For example, in the packaging of precision optical sensors, the material needs to be able to withstand certain mechanical deformation without damage while ensuring good light transmission. Elastic ceramics are new materials developed to overcome the limitations of traditional materials. They can integrate the advantages of ceramics and transparent materials. Through special preparation processes and component design, they have high transmittance and elastic deformation capabilities similar to rubber, thereby expanding the application potential of materials in multiple fields and promoting the further development of related technologies.

[0004] Elastic ceramics break the traditional concept that optical ceramics have poor elasticity, thus opening up a new field of ceramic preparation and application. Elastic ceramics have excellent properties and potential applications in many fields, and have attracted more and more attention from scholars and scientists in recent years.

[0005] Si et al. (Chemical Engineering Journal, 2022, 433, 133628.) used the composite phase ZrO2-YO 1.5 -TaO 2.5 Ceramics, the effect of m-YTaO4 phase and t-ZrO2 phase on the elastic modulus of ceramics was studied, and the elastic modulus reached up to 112.8GPa. This shows that elastic ceramics have great potential, but the final result did not reach a good elastic performance data.

[0006] A Chinese patent (CN 118580081 A) discloses a silicon-silicon carbide ceramic with a high elastic modulus, which is formed by dry pressing, isostatic pressing or casting. The gel casting molding adopted in this scheme can prepare complex shapes compared to dry pressing, has lower costs than isostatic pressing, and has higher production efficiency than casting.

[0007] Chinese patent (CN 116768648 A) discloses a three-dimensional network micro-nanostructured silicon-based precursor ultra-high temperature elastic ceramic, preparation method and application, which are mainly used in the fields of aerospace, chemical metallurgy and nuclear power generation. Chinese patent (CN114956858 A) discloses a layered elastic-plastic silicon nitride ceramic and its preparation method, which are mainly used in the fields of ceramic engines, fighter jet nozzles, etc. Chinese patent (CN118957885 A) discloses a preparation method of an elastic ceramic nanofiber membrane material, which is mainly used in the fields of national defense, aerospace, flexible electronics, etc. Chinese patent (CN118109967 A) discloses an elastic ceramic nanofiber membrane composed of curled fibers, its preparation method and application, which are mainly used in the fields of aerospace, national defense and military. The present invention is applied to the field of optical sensors.

[0008] In summary, it is necessary to focus on the elasticity of ceramic functional systems and realize the application of the excellent elastic properties of ceramics in optical instruments, which is of great significance for solving the packaging protection problem of optical sensors. Summary of the invention

[0009] In order to solve the above problems, the present invention proposes a preparation method and application of a highly elastic RAG:W elastic ceramic. The RAG:W elastic ceramic prepared by the present invention has the characteristics of large size, complex shape, and good elastic performance. Different combinations of R and W of the elastic ceramic can be applied to different occasions. The preparation method of the present invention has the advantages of simple process, good controllability, no need for sintering aids, relatively simple sintering conditions, easy operation and production, etc.

[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions: A highly elastic RAG:W elastic ceramic, the raw material components of the elastic ceramic are RAG and W oxides, wherein the chemical formula of RAG is R3Al5O 12 , has a cubic garnet structure, R is an element that can replace yttrium in the cubic structure of yttrium aluminum garnet and stabilize the cubic garnet structure, such as gadolinium (Gd), dysprosium (Dy) or lutetium (Lu), etc., W is europium (Eu 3+ ), Ytterbium (Yb 3+ ) or neodymium (Nd 3+ ), wherein the elastic modulus of the elastic ceramic is 300-400MPa.

[0011] The preparation method of the high elastic RAG:W elastic ceramic of the present invention comprises the following steps: 12W is introduced into the main component to form RAG:W elastic ceramics. The elastic ceramics are prepared by AM gel casting combined with inorganic calcium carbonate oligomer (CCO) and organic covalent lipoic acid (TA). When the ceramic blank is prepared by gel casting, the monomer is acrylamide (AM); the cross-linking agent is N,N'-methylenebisacrylamide (MBAM); the dispersant is ammonium citrate (TAC); the pH regulator is tetramethylammonium hydroxide (TMAH); the initiator is ammonium persulfate solution (APS); specifically, the following steps are included: (1) Preparation of RAG:W precursor powder: W oxide powder W2O3, R oxide powder R2O3 and alumina powder Al2O3 are mixed in a certain stoichiometric ratio to obtain oxide mixed powder, and fine powder is obtained after ball milling, drying, grinding and sieving. CCO is added to an ethanol solution of TA, and the ethanol solution containing CCO and TA is added to the fine powder. The fine powder is then calcined once to obtain a RAG:W powder mixture. After cooling to room temperature, the RAG:W powder mixture is subjected to the same ball milling, drying, grinding and sieving as above, and the ground and sieved powder is calcined twice to finally obtain a uniform RAG:W precursor powder with good sintering activity; (2) preparing a slurry: adding the RAG:W precursor powder obtained in step (1) into a ball mill, placing alumina grinding balls and deionized water into the ball mill, and then adding monomer acrylamide and crosslinking agent N,N'-methylenebisacrylamide, dispersant ammonium citrate and pH adjuster tetramethylammonium hydroxide solution for ball milling to obtain a slurry; (3) Preparing a green blank: Wait for the slurry in step (2) to be evenly dispersed by ball milling, pour the slurry into a defoaming tank through a sieve, add a catalyst, put it into a vacuum defoamer to defoam, add an initiator, stir evenly to avoid introducing bubbles, then inject it into a mold, let it stand and dry in a drying oven to obtain a ceramic green blank, demold it after drying, and put the demolded green blank into a muffle furnace for debinding; (4) Preparation of RAG:W elastic ceramics: The debinded ceramics obtained in step (3) are placed in a vacuum sintering furnace to obtain pure phase elastic ceramics, and the pure phase elastic ceramics are annealed and polished to finally obtain RAG:W elastic ceramics.

[0012] Furthermore, in the step (1), the oxide powder R2O3 of R, the aluminum oxide powder Al2O3 and the oxide powder W2O3 of W are all high-purity oxides with a powder purity of >99.9%, the molar ratio of the R2O3, Al2O3 and W2O3 powders is 3:5:(0.01-0.1), the mass percentage of calcium carbonate oligomer in the oxide mixed powder is 1-3wt%, the mass percentage of organic covalent lipoic acid in the oxide mixed powder is 0.4-0.8wt%, and the mass percentage of ethanol solution in the oxide mixed powder is 5-10wt%.

[0013] Furthermore, in the step (1), the ball milling adopts a nylon ball milling jar with alcohol as the solvent, the mass ratio of the ball medium to the oxide mixed powder is 2:1, the rotation speed of the ball mill is 160-170 r / min, and the ball milling time is 20-24 h; the drying temperature is 70-80° C., and the drying time is 20-24 h; in the step (1), the primary calcination temperature is 1100-1400° C., the primary calcination time is 2-4 h, the secondary calcination temperature is 800-1000° C., the secondary calcination time is 2-4 h, the heating rate during the primary calcination and the secondary calcination is 5-8° C. / min, and the cooling rate during the primary calcination and the secondary calcination is 5-10° C. / min.

[0014] Furthermore, in the step (2), the RAG:W precursor powder is added to the ball mill twice, the ball milling time is 3 to 5 hours, the mass percentage of acrylamide in the RAG:W precursor powder is 2 to 4 wt%, the mass percentage of N,N'-methylenebisacrylamide in the RAG:W precursor powder is 0.1 to 0.2 wt%, the mass percentage of ammonium citrate in the RAG:W precursor powder is 0.02 to 0.04 wt%, the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution in the RAG:W precursor powder is 1.0 to 1.1 wt%, and the solid content of the obtained slurry is 45 to 55 wt%.

[0015] Furthermore, in the step (3), the catalyst is a tetramethylethylenediamine solution, wherein the tetramethylethylenediamine in the tetramethylethylenediamine solution accounts for 15-25wt% of the mass of the RAG:W precursor powder; the initiator is an ammonium persulfate solution, wherein the ammonium persulfate in the ammonium persulfate solution accounts for 3-5wt% of the mass of the RAG:W precursor powder; the defoaming time in the vacuum defoamer in the step (3) is 30-60 minutes; and the drying is carried out in a drying oven at 40°C and 80°C for 20-24 hours respectively.

[0016] Furthermore, in the step (3), the specific steps of debinding the green billet after demoulding are: firstly, calcining the green billet at 120-200°C for 6-8h, then cooling to room temperature, with a heating and cooling rate of 0.5-1°C / min; then, debinding the green billet at 400-500°C for 6-8h, then cooling to room temperature, with a heating and cooling rate of 1-2°C / min; finally, debinding the green billet at 700-800°C for 6-8h, then cooling to room temperature, with a heating and cooling rate of 1-2°C / min.

[0017] Furthermore, the vacuum degree during sintering in step (4) is greater than 5.0 × 10 -4 Pa, specifically 10 -2 ~10 -4Pa, the sintering temperature is 1700-1900℃, and the sintering time is 10-12h.

[0018] Furthermore, the annealing treatment in step (4) is carried out in an air atmosphere, the annealing temperature is 1300-1500° C., and the annealing time is 3-5 hours.

[0019] The present invention also provides the application of the RAG:W elastic ceramic in the field of optical sensors. Although traditional ceramics have the advantages of high hardness, excellent high temperature resistance and good chemical stability, their brittleness is an obvious defect. During the packaging process of the optical sensor and the use of the sensor, stress may be generated due to factors such as temperature changes and mechanical stress. Elastic ceramics can buffer and absorb these stresses to a certain extent, reduce the impact of stress on the performance and structure of the optical sensor, and improve the reliability and stability of the sensor. The RAG:W elastic ceramics prepared by the AM gel injection molding process and inorganic calcium carbonate oligomers (CCO) and organic covalent lipoic acid (TA) provided by the present invention realize the preparation of large-size and complex-shaped RAG:W elastic ceramics, which can meet the application requirements of elastic ceramics in optical sensor packaging.

[0020] The present invention combines the advantages of ceramics, and products made of this material can maintain good performance under complex and changeable environmental conditions. It can provide good mechanical support and protection for the internal sensitive components of optical sensors to prevent them from being damaged when subjected to external impact, vibration or extrusion. When the device is accidentally dropped in some portable optical sensor devices, the elastic ceramic package can effectively buffer the impact force, protect the core components of the sensor, reduce the frequency of equipment maintenance and replacement, and thus improve the reliability and economy of the entire system.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of RAG:W elastic ceramics proposed in the present invention adopts AM gel injection molding process and inorganic calcium carbonate oligomer (CCO) and organic covalent lipoic acid (TA) method to form TA-CCO hybrid molecules to prepare elastic ceramics. The material can absorb and disperse stress to a certain extent. When the material is subjected to external force, it can buffer the force through elastic deformation and reduce the risk of crack propagation caused by stress concentration, which helps to improve the material's resistance to deformation. When it is subjected to pressure or impact, it can use its own elasticity, like a "buffer", to avoid damage to the structure due to instantaneous huge external force, thereby extending the service life of the material and structure. The elastic modulus is as high as 300-400MPa, and its elastic properties are far superior to general ceramics.

[0022] (2) The present invention is the first to use the AM gel injection molding process to add inorganic calcium carbonate oligomers and organic covalent lipoic acid to form a TA-CCO structure to prepare RAG:W elastic ceramics. Elastic ceramics can effectively prevent the expansion of cracks. When tiny cracks appear in the material, its elasticity can absorb the energy of crack expansion, making it difficult for the crack to extend further, thereby avoiding sudden breakage of the material.

[0023] (3) The material prepared by adding inorganic calcium carbonate oligomers and organic covalent lipoic acid in the AM gel injection molding process in the method of the present invention has elasticity that enables it to resist deformation to a certain extent. When subjected to external forces (such as slight collisions, stress caused by temperature changes, etc.), it can still maintain good optical properties, ensuring the clarity and accuracy of imaging.

[0024] (4) The material prepared by adding inorganic calcium carbonate oligomer and organic covalent lipoic acid in the AM gel injection molding process in the method of the present invention generally has a low thermal expansion coefficient. This means that its size changes less when the temperature changes. Elastic ceramics can be used as substrate materials in electronic devices under high temperature environments. Compared with other materials with large thermal expansion coefficients, they can better maintain the connection stability between electronic components and prevent poor contact between components or circuit damage due to thermal expansion.

[0025] (5) The material prepared by adding inorganic calcium carbonate oligomer and organic covalent lipoic acid in the AM gel injection molding process in the method of the present invention has a certain heat insulation ability. It can form a thermal barrier between high temperature and low temperature environments to slow down the transfer of heat. It can effectively reduce the thermal impact of external high temperature on the internal equipment and structure of the sensor, ensuring that the equipment works normally within the appropriate temperature range. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 It is a process flow chart of the present invention.

[0028] Figure 2 shows the GdAG:Eu prepared in Example 1 of the present invention 3+ Elastic ceramics, GdAG:Eu prepared in Comparative Example 1 3+ Elastic ceramics, GdAG:Eu prepared in Example 2 3+ Elastic ceramics, GdAG:Eu prepared in Example 3 3+Comparison of the elastic modulus of elastic ceramics and the springback rate at 10% deformation. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] In the following embodiments, the mass percentage purity of the raw material W2O3 oxide powder of W is ≥99.9%; the mass percentage purity of the raw material R2O3 oxide powder of R is ≥99.9%; and the mass percentage purity of the raw material Al2O3 oxide powder is ≥99.9%.

[0031] Example 1 A GdAG:Eu 3+ Preparation methods of elastic ceramics, such as Figure 1 As shown, the specific steps are: (1) Prepare 60 g of GdAG:Eu 3+ The ceramic powders are respectively weighed as gadolinium oxide powder Gd2O3, aluminum oxide powder Al2O3 and europium oxide powder Eu2O3, with a molar ratio of 3:5:0.1, and added into a nylon ball mill with alcohol as solvent for 24 hours to obtain a uniform oxide mixed powder, the mass ratio of the ball medium to the oxide mixed powder (i.e., the ball-to-material ratio) is 2:1, and the rotation speed of the ball mill is 170r / min; the oxide mixed powder slurry is separated and dried at 80°C for 24 hours, the dried powder is ground and sieved, CCO (3wt%, relative to powder) is added to TA (0.8wt%, relative to powder) in an alcohol solvent (10wt%, relative to powder), the solution is added to the refined powder, and the refined powder is then placed in a muffle furnace and calcined at 1100°C for 4 hours to obtain GdAG:Eu 3+ The powder mixture was heated at a rate of 8°C / min and cooled at a rate of 10°C / min. 3+ The powder mixture was ball-milled, dried, and sieved in the same manner as above, and then the sieved powder was placed in a muffle furnace and calcined at 1000°C for 4 h, with a heating rate of 8°C / min and a cooling rate of 10°C / min, to finally obtain a uniform GdAG:Eu with good sintering activity. 3+ Precursor powder; (2) Slurry preparation: AM gel casting process was used to obtain GdAG:Eu 3+ The specific process is as follows: GdAG:Eu obtained in step (1) 3+The precursor powder was added into a ball mill containing acrylamide (2wt%, relative to the powder), N,N'-methylenebisacrylamide (0.1wt%, relative to the powder), ammonium citrate (0.25wt%, relative to the powder), tetramethylammonium hydroxide solution (1.00wt%, relative to the powder), pure water (so that the final slurry solid content is 55wt%), and alumina grinding balls, and then ball milled for 5h. GdAG:Eu 3+ The precursor powder can be added in two batches.

[0032] (3) Preparation of green blank: Wait for the slurry from step (2) to be evenly dispersed by ball milling, pour the slurry into a defoaming tank using a strainer, and use a pipette to prepare a catalyst tetramethylethylenediamine solution (25wt%, relative to the powder) and an initiator ammonium persulfate solution (5wt%, relative to the powder). The solution may become ineffective over time, so prepare 10 ml and do not leave it for too long, usually 1 day. Then, 120 microliters of tetramethylethylenediamine solution was added as catalyst, and the mixture was placed in a vacuum degassing machine for degassing for 30 minutes. 240 microliters of ammonium persulfate solution as initiator was added, and the slurry was injected into a circular mold. The green blank was placed in a 40°C and 80°C drying oven for 24 hours respectively, and then demolded. The demolded green blank was placed in a muffle furnace for debinding. The green blank was first fired at 200°C for 8 hours, and then cooled to room temperature at a heating and cooling rate of 1°C / min; then the green blank was fired at 500°C for 8 hours, and then cooled to room temperature at a heating and cooling rate of 1°C / min; finally, the green blank was fired at 800°C for 8 hours, and then cooled to room temperature at a heating and cooling rate of 1°C / min. Subsequently, a dense green blank was obtained.

[0033] (4) Sintering: Sinter the GdAG:Eu prepared in step (3) 3+ The dense green billet is placed in a vacuum of 10 -2 Pa vacuum environment, sintered at 1900 °C for 10 h to obtain pure phase ceramics; (5) Post-annealing treatment: The sintered pure phase ceramic sample was kept at 1500°C for 3 h in an air atmosphere and polished to obtain GdAG:Eu with an elastic modulus of 300 MPa. 3+ Elastic ceramics.

[0034] Example 2 A GdAG:Eu 3+ Preparation methods of elastic ceramics, such as Figure 1 As shown, the specific steps are: (1) Prepare 60 g of GdAG:Eu 3+The ceramic powders are respectively weighed as gadolinium oxide powder Gd2O3, aluminum oxide powder Al2O3 and europium oxide powder Eu2O3, with a molar ratio of 3:5:0.05, and added into a nylon ball mill with alcohol as solvent for 22 hours to obtain a uniform oxide mixed powder, the mass ratio of the ball medium to the oxide mixed powder (i.e., the ball-to-material ratio) is 2:1, and the rotation speed of the ball mill is 165r / min; the oxide mixed powder slurry is separated and dried at 75°C for 24 hours, the dried powder is ground and sieved, CCO (2wt%, relative to the powder) is added to TA (0.6wt%, relative to the powder) in an alcohol solvent (8wt%, relative to the powder), the solution is added to the refined powder, and the refined powder is then placed in a muffle furnace and calcined at 1200°C for 3 hours to obtain GdAG:Eu 3+ The powder mixture was heated at a rate of 6°C / min and cooled at a rate of 8°C / min. 3+ The powder mixture was ball-milled, dried, and sieved in the same manner as above, and then the sieved powder was placed in a muffle furnace and calcined at 900 °C for 3 h, with a heating rate of 6 °C / min and a cooling rate of 8 °C / min, to finally obtain a uniform GdAG:Eu with good sintering activity. 3+ Precursor powder; (2) Slurry preparation: AM gel casting process was used to obtain GdAG:Eu 3+ The specific process is as follows: GdAG:Eu obtained in step (1) 3+ The precursor powder was added into a ball mill containing acrylamide (2.5wt%, relative to the powder), N,N'-methylenebisacrylamide (0.1wt%, relative to the powder), ammonium citrate (0.35wt%, relative to the powder), tetramethylammonium hydroxide solution (1.05wt%, relative to the powder), pure water (so that the final slurry solid content is 50wt%), and alumina grinding balls, and then ball milled for 4h. GdAG:Eu 3+ The precursor powder can be added in two batches.

[0035] (3) Preparation of green blank: Wait for the slurry in step (2) to be evenly dispersed by ball milling, pour the slurry into a defoaming tank with a sieve, prepare a catalyst tetramethylethylenediamine (20wt%, relative to powder) solution and an initiator ammonium persulfate (4wt%, relative to powder) solution with a pipette gun, then add 120 μL of the above-prepared catalyst, put it into a vacuum defoamer for defoaming for 45 minutes, add 240 μL of initiator, inject the slurry into a round mold, and then put the green blank into a 40℃ and 80℃ drying oven for 22 hours respectively, then demold it, put the demolded green blank into a muffle furnace for debinding, first burn the green blank at 160℃ for 7 hours, then cool it to room temperature, and the heating and cooling rate is 1℃ / min; then burn the green blank at 450℃ for 7 hours, then cool it to room temperature, and the heating and cooling rate is 1℃ / min; finally, burn the green blank at 800℃ for 8 hours, then cool it to room temperature, and the heating and cooling rate is 2℃ / min. Subsequently, a dense green blank is obtained.

[0036] (4) Sintering: Sinter the GdAG:Eu prepared in step (3) 3+ The dense green billet is placed in a vacuum of 10 -3 Pa vacuum environment, sintered at 1800 °C for 11 hours to obtain pure phase ceramics; (5) Annealing treatment: The sintered pure phase ceramic sample was kept at 1400°C for 4 h in an air atmosphere and polished to obtain GdAG:Eu with an elastic modulus of 350 MPa. 3+ Elastic ceramics.

[0037] Example 3 A GdAG:Eu 3+ Preparation methods of elastic ceramics, such as Figure 1 As shown, the specific steps are: (1) Prepare 60 g of GdAG:Eu 3+ The ceramic powders are respectively weighed as gadolinium oxide powder Gd2O3, aluminum oxide powder Al2O3 and europium oxide powder Eu2O3, with a molar ratio of 3:5:0.01, and added into a nylon ball mill with alcohol as solvent for 20 hours to obtain a uniform oxide mixed powder, the mass ratio of the ball medium to the oxide mixed powder (i.e., the ball-to-material ratio) is 2:1, and the rotation speed of the ball mill is 160r / min; the oxide mixed powder slurry is separated and dried at 70°C for 24 hours, the dried powder is ground and sieved, CCO (1wt%, relative to the powder) is added to TA (0.4wt%, relative to the powder) in an alcohol solvent (5wt%, relative to the powder), the solution is added to the refined powder, and the refined powder is then placed in a muffle furnace and calcined at 1400°C for 2 hours to obtain GdAG:Eu 3+ The powder mixture was heated at a rate of 5°C / min and cooled at a rate of 5°C / min.3+ The powder mixture was ball-milled, dried, and sieved in the same manner as above, and then the sieved powder was placed in a muffle furnace and calcined at 800 °C for 2 h, with a heating rate of 5 °C / min and a cooling rate of 5 °C / min, to finally obtain a uniform GdAG:Eu with good sintering activity. 3+ Precursor powder; (2) Slurry preparation: AM gel casting process was used to obtain GdAG:Eu 3+ The specific process is as follows: GdAG:Eu obtained in step (1) 3+ The precursor powder was added into a ball mill containing acrylamide (3wt%, relative to the powder), N,N'-methylenebisacrylamide (0.1wt%, relative to the powder), ammonium citrate (0.50wt%, relative to the powder), tetramethylammonium hydroxide solution (1.10wt%, relative to the powder), pure water (so that the solid content of the final slurry is 45wt%), and alumina grinding balls, and then ball milled for 3h. GdAG:Eu 3+ The precursor powder can be added in two batches.

[0038] (3) Preparation of green blank: Wait for the slurry of step (2) to be evenly dispersed by ball milling, pour the slurry into a defoaming tank with a sieve, prepare a catalyst tetramethylethylenediamine (15wt%, relative to powder) solution and an initiator ammonium persulfate (3wt%, relative to powder) solution with a pipette, filter the slurry through the ball mill, add 120 μL of the prepared catalyst, place it in a vacuum defoamer for defoaming for 60 min, add 240 μL of the initiator, inject the slurry into a circular mold, and then place the green blank in a 40°C and 80°C drying oven for 20 h respectively, then demold it, place the demolded green blank in a muffle furnace for debinding, first calcine the green blank at 120°C for 6 h, then cool it to room temperature, with a heating and cooling rate of 0.5°C / min; then debind the green blank at 400°C for 6 h, then cool it to room temperature, with a heating and cooling rate of 2°C / min; finally, debind the green blank at 700°C for 6 h, then cool it to room temperature, with a heating and cooling rate of 2°C / min. Subsequently, a dense green body is obtained.

[0039] (4) Sintering: Sinter the GdAG:Eu prepared in step (3) 3+ The dense green billet is placed in a vacuum of 10 -4 Pa vacuum environment, sintered at 1700 °C for 12 h to obtain pure phase ceramics; (5) Annealing treatment: The sintered pure phase ceramic sample was kept at 1300°C for 5 h in air atmosphere and polished to obtain GdAG:Eu with an elastic modulus of 400 MPa. 3+ Elastic ceramics.

[0040] Comparative Example 1 A GdAG:Eu3+ The preparation method of elastic ceramics comprises the following specific steps: (1) Prepare 60 g of GdAG:Eu 3+ The ceramic powders were weighed in a molar ratio of 3:5:0.1 for gadolinium oxide powder Gd2O3, aluminum oxide powder Al2O3 and europium oxide powder Eu2O3, respectively, and added into a nylon ball mill with alcohol as solvent for 24 hours to obtain a uniform oxide mixed powder, the mass ratio of the ball medium to the oxide mixed powder (i.e., the ball-to-material ratio) was 2:1, and the rotation speed of the ball mill was 170 r / min; the oxide mixed powder slurry was separated and dried at 80°C for 24 hours, and then the refined powder was placed in a muffle furnace and calcined at 1100°C for 4 hours to obtain GdAG:Eu 3+ The powder mixture was heated at a rate of 8°C / min and cooled at a rate of 10°C / min. 3+ The powder mixture was ball-milled, dried, and sieved in the same manner as above, and then the sieved powder was placed in a muffle furnace and calcined at 1000°C for 4 h, with a heating rate of 8°C / min and a cooling rate of 10°C / min, to finally obtain a uniform GdAG:Eu with good sintering activity. 3+ Precursor powder; (2) Slurry preparation: AM gel casting process was used to obtain GdAG:Eu 3+ The specific process is as follows: GdAG:Eu obtained in step (1) 3+ The precursor powder was added into a ball mill containing acrylamide (2wt%, relative to the powder), N,N'-methylenebisacrylamide (0.1wt%, relative to the powder), ammonium citrate (0.25wt%, relative to the powder), tetramethylammonium hydroxide solution (1.00wt%, relative to the powder), pure water (so that the final slurry solid content is 55wt%), and alumina grinding balls, and then ball milled for 5h. GdAG:Eu 3+ The precursor powder can be added in two batches.

[0041] (3) Preparation of green blank: Wait for the slurry from step (2) to be evenly dispersed by ball milling, pour the slurry into a defoaming tank using a strainer, and use a pipette to prepare a solution of catalyst tetramethylethylenediamine (25wt%, relative to powder) and an initiator ammonium persulfate (5wt%, relative to powder). The solution may become ineffective over time, so prepare 10 ml and do not leave it for too long, usually 1 day. Then add 120 microliters of catalyst, put it in a vacuum degassing machine to degas for 30 minutes, add 240 microliters of initiator, and then inject the slurry into a round mold, dry the slurry at room temperature for two days to completely demould the blank, then put the blank into a 40℃ and 80℃ drying oven for 24 hours respectively, put the dried blank into a muffle furnace for debinding, first burn the blank at 200℃ for 8 hours, then cool it to room temperature, and the heating and cooling rate is 1℃ / min; then discharge the blank at 500℃ for 8 hours, and then cool it to room temperature, and the heating and cooling rate is 1℃ / min; finally discharge the blank at 800℃ for 8 hours, and then cool it to room temperature, and the heating and cooling rate is 1℃ / min. Subsequently, a dense blank is obtained.

[0042] (4) Sintering: Sinter the GdAG:Eu prepared in step (3) 3+ The dense green billet is placed in a vacuum of 10 -2 Pa vacuum environment, sintered at 1900 °C for 10 h to obtain pure phase ceramics; (5) Post-annealing treatment: The sintered pure phase ceramic sample was kept at 1500°C for 3 h in an air atmosphere and polished to obtain GdAG:Eu with an elastic modulus of 20 GPa. 3+ Elastic ceramics.

[0043] Depend on Figure 2 It can be seen that in Example 1, Example 2 and Example 3, by adding CCO and TA to form TA-CCO hybrid molecules, the elastic properties of the elastic ceramics have been significantly changed, that is, the elastic modulus is reduced and the rebound efficiency is improved. By comparing Example 1 with Comparative Example 1, it can be seen that the rebound rate under the same degree of deformation has been significantly improved, and in the three examples, the rebound rate has reached more than 80%. This proves that the preparation method provided by the present invention, that is, the method of using AM gel injection molding combined with CCO and TA, can improve the relevant properties of the prepared elastic ceramics.

[0044] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A highly elastic RAG:W elastic ceramic, characterized in that: The raw materials of elastic ceramics are RAG and W oxides, where the chemical formula of RAG is R3Al5O 12 , has a cubic garnet structure, R is one of gadolinium (Gd), dysprosium (Dy) or lutetium (Lu), W is europium (Eu 3+ ), Ytterbium (Yb 3+ ) or neodymium (Nd 3+ ), wherein the elastic modulus of the elastic ceramic is 300-400MPa.

2. The method for preparing the highly elastic RAG:W elastic ceramic according to claim 1, characterized in that: The elastic ceramic is prepared by using AM gel casting combined with inorganic calcium carbonate oligomer (CCO) and organic covalent lipoic acid (TA), comprising the following steps: (1) Preparation of RAG:W precursor powder: W oxide powder W2O3, R oxide powder R2O3 and alumina powder Al2O3 are mixed in a certain stoichiometric ratio to obtain oxide mixed powder, and fine powder is obtained after ball milling, drying, grinding and sieving. CCO is added to an ethanol solution of TA, and the ethanol solution containing CCO and TA is added to the fine powder. The fine powder is then calcined once to obtain a RAG:W powder mixture. After cooling to room temperature, the RAG:W powder mixture is subjected to the same ball milling, drying, grinding and sieving as above, and the ground and sieved powder is calcined twice to finally obtain a uniform RAG:W precursor powder with good sintering activity; (2) preparing a slurry: adding the RAG:W precursor powder obtained in step (1) into a ball mill, placing alumina grinding balls and deionized water into the ball mill, and then adding monomer acrylamide and crosslinking agent N,N'-methylenebisacrylamide, dispersant ammonium citrate and pH adjuster tetramethylammonium hydroxide solution for ball milling to obtain a slurry; (3) Preparing a green blank: Wait for the slurry in step (2) to be evenly dispersed by ball milling, pour the slurry into a defoaming tank through a sieve, add a catalyst, put it into a vacuum defoamer to defoam, add an initiator, stir evenly to avoid introducing bubbles, then inject it into a mold, let it stand and dry in a drying oven to obtain a ceramic green blank, demold it after drying, and put the demolded green blank into a muffle furnace for debinding; (4) Preparation of RAG:W elastic ceramics: The debinded ceramics obtained in step (3) are placed in a vacuum sintering furnace to obtain pure phase elastic ceramics, and the pure phase elastic ceramics are annealed and polished to finally obtain RAG:W elastic ceramics.

3. The method for preparing the highly elastic RAG:W elastic ceramic according to claim 1, characterized in that: In the step (1), the oxide powder R2O3 of R, the aluminum oxide powder Al2O3 and the oxide powder W2O3 of W are all high-purity oxides with a powder purity of >99.9%. The molar ratio of the R2O3, Al2O3 and W2O3 powders is 3:5:(0.01-0.1), the mass percentage of calcium carbonate oligomer in the oxide mixed powder is 1-3wt%, the mass percentage of organic covalent lipoic acid in the oxide mixed powder is 0.4-0.8wt%, and the mass percentage of ethanol solution in the oxide mixed powder is 5-10wt%.

4. The method for preparing the highly elastic RAG:W elastic ceramic according to claim 1, characterized in that: In the step (1), the ball milling adopts a nylon ball milling jar with alcohol as the solvent, the mass ratio of the ball medium to the oxide mixed powder is 2:1, the rotation speed of the ball mill is 160-170r / min, and the ball milling time is 20-24h; the drying temperature is 70-80°C, and the drying time is 20-24h; in the step (1), the primary calcination temperature is 1100-1400°C, the primary calcination time is 2-4h, the secondary calcination temperature is 800-1000°C, the secondary calcination time is 2-4h, the heating rate during the primary calcination and the secondary calcination is 5-8°C / min, and the cooling rate during the primary calcination and the secondary calcination is 5-10°C / min.

5. The method for preparing the highly elastic RAG:W elastic ceramic according to claim 1, characterized in that: In the step (2), the RAG:W precursor powder is added to the ball mill twice, the ball milling time is 3-5 hours, the mass percentage of acrylamide in the RAG:W precursor powder is 2-4wt%, the mass percentage of N,N'-methylenebisacrylamide in the RAG:W precursor powder is 0.1-0.2wt%, the mass percentage of ammonium citrate in the RAG:W precursor powder is 0.02-0.04wt%, the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution in the RAG:W precursor powder is 1.0-1.1wt%, and the solid content of the obtained slurry is 45-55wt%.

6. The method for preparing the highly elastic RAG:W elastic ceramic according to claim 1, characterized in that: In the step (3), the catalyst is a tetramethylethylenediamine solution, wherein the tetramethylethylenediamine in the tetramethylethylenediamine solution accounts for 15-25wt% of the mass of the RAG:W precursor powder; the initiator is an ammonium persulfate solution, wherein the ammonium persulfate in the ammonium persulfate solution accounts for 3-5wt% of the mass of the RAG:W precursor powder; the defoaming time in the vacuum defoamer in the step (3) is 30-60 minutes; and the drying is carried out in a drying oven at 40°C and 80°C for 20-24 hours respectively.

7. The method for preparing the highly elastic RAG:W elastic ceramic according to claim 1, characterized in that: In the step (3), the specific steps of debinding the green billet after demoulding are: first, the green billet is fired at 120-200°C for 6-8 hours, then cooled to room temperature, and the heating and cooling rates are 0.5-1°C / min; then, the green billet is debinded at 400-500°C for 6-8 hours, and then cooled to room temperature, and the heating and cooling rates are 1-2°C / min; finally, the green billet is debinded at 700-800°C for 6-8 hours, and then cooled to room temperature, and the heating and cooling rates are 1-2°C / min.

8. The method for preparing the highly elastic RAG:W elastic ceramic according to claim 1, characterized in that: The vacuum degree during sintering in step (4) is greater than 5.0×10 -4 Pa, specifically 10 -2 ~10 -4 Pa, the sintering temperature is 1700-1900℃, and the sintering time is 10-12h.

9. The method for preparing the highly elastic RAG:W elastic ceramic according to claim 1, characterized in that: The annealing treatment in step (4) is carried out in an air atmosphere, the annealing temperature is 1300-1500° C., and the annealing time is 3-5 hours.

10. The highly elastic RAG:W elastic ceramics according to claim 1 are used in the field of optical sensors.

Citation Information

Patent Citations

  • Layered elastic-plastic silicon nitride ceramic and preparation method thereof

    CN114956858A

  • Three-dimensional network micro-nano structure silicon-based precursor ultra-high-temperature elastic ceramic, preparation method and application

    CN116768648A

  • Elastic ceramic nanofiber membrane formed by crimped fibers and preparation method and application thereof

    CN118109967A

  • Silicon-silicon carbide ceramic material with high elastic modulus

    CN118580081A

  • Preparation method of elastic ceramic nanofiber membrane material

    CN118957885A